Signifikansi Nilai-Nilai Pendidikan Multikultural dalam Ajaran Agama Buddha - Arif Muzayin Shofwan (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Buddhism is a religion that aims to bring happiness to all living beings through mutual respect, acceptance, celebrating differences, and living peacefully. Of course, this kind of thing is in accordance with multicultural education, one of the aims of which is to develop the ability to recognize, accept, appreciate and celebrate cultural diversity. This qualitative research using literature studies analyzes the significance of multicultural education values ​​in Buddhist teachings. The data analysis technique uses content analysis by sorting things according to the focus and objectives of the research. This research produces the following three conclusions. First, Buddhism teaches tolerance so that its followers can listen to the teachings of other religions with full awareness as stated in